ANALISIS IMPLEMENTASI AKUNTANSI PEMBIAYAAN MUSYARAKAH BERDASARKAN PERNYATAAN STANDAR AKUNTANSI (PSAK) 106 DI BMT HARUM TULUNGAGUNG - Laidiana Fauqol Ngadati Mahiro; Sri Dwi Estiningrum (Jurnal Akuntansi dan Pajak, 2022)
This research is motivated by the phenomenon that in practice musyarakah financing products in Islamic financial institutions have not been implemented properly, there are some confusions during accounting measurement and presentation and there are still some practical problems that are suggested to be resolved in accordance with the objectives of the implementation of the musyarakah contract. Research on musyarakah contracts is mostly done in Islamic Bank financial institutions, while in financial institutions such as Baitul Maal wa Tamwil (BMT) it is still rarely done. This study aims to determine the suitability of the application of musharaka accounting at BMT Harum Tulungagung based on PSAK No. 106. This research is a case study research using a qualitative approach. Data analysis was carried out by means of descriptive data analysis. The results of this study indicate that the Musyarakah financing of BMT Harum Tulungagung is not fully in accordance with PSAK 106. The analysis of the suitability of the application of musyarakah accounting based on PSAK 106 shows that the recognition and measurement of Musyarakah financing is in accordance with PSAK 106. However, the presentation and disclosure is not fully in accordance with PSAK. 106 because cash handed over to active partners is presented as musyarakah financing and the presentation of the recording of financing is not in accordance with PSAK 106 because the active partner only keeps a simple record. Keywords: Musyarakah, Sharia Accounting, PSAK No. 106